THE INFLUENCE OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT GENERAL ELECTION COMMISSION IN SOUTH SULAWESI PROVINCE - Alfina Mutya; Abdul Wahid; Lely Novia (International Journal of Business English and Communication, 2023)
This study aims to determine the influenced of the Working Environment on employee performance at the General Election Commission in South Sulawesi Province. The population in this Research is all employees consist of 37 people. The number of samples used were 37 people using total sampling theory. The data were collected by using the description method and questionnaires distribution. The data analysis technique used is simple linear regression analysis using Statistic application. The result of this study indicate that the Working Environment variable has a positive and significant influenced on Employee Performance variables, with a significant value about 0.001, and coefficient value about 0.405. Testing results of t value is 5.461 bigger than the t table > 2.030. It can be concluded that there is a positive and significant connection between the working environment and employee performance at the General Election Commission in South Sulawesi Province. The influence of the work environment on employee performance is 46%, while 54% is influenced by an unknown variable or variables not examined in this research.